2016
DOI: 10.5578/keg.9786
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Creativity Among Children in Kindergartens, Primary, Middle and High Schools

Abstract: This study, which has a correlational survey design, aims to investigate creativity among children in kindergartens, primary, middle and high schools. The population of this study is comprised of all children attending kindergartens, primary, middle and high schools in the 2011-2012 academic years. The sample of the study consisted of a total of 1200 students, 100 of whom were randomly selected from each level of education. For some reasons, some cases were omitted, and analyses were done using the data of 108… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Mullineaux and Lisabeth F. DiLalla (2009), they stated that elaboration scores of 10-15 year-old girls were higher than boys' elaboration scores and girls' drawings were better and more innovative. In their study, Aysel Köksal Akyol and Güneş Salı (2016) found that there was a significant difference between the grade levels in terms of ATs and the creativity mean score of the girls attending high school was higher than boys.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 92%
See 4 more Smart Citations
“…Mullineaux and Lisabeth F. DiLalla (2009), they stated that elaboration scores of 10-15 year-old girls were higher than boys' elaboration scores and girls' drawings were better and more innovative. In their study, Aysel Köksal Akyol and Güneş Salı (2016) found that there was a significant difference between the grade levels in terms of ATs and the creativity mean score of the girls attending high school was higher than boys.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 92%
“…As the grade level rises, the age increases and this result can be interpreted as the fact that as the grade level increases, detailing (elaboration) enhanced. In a cross-sectional study conducted at the level of the grades, it was found that the elaboration scores was the highest in the 5th, 6th, 9th, and 10th grades (Köksal Akyol & Salı, 2016). There was no significant difference in the scores of originality and ATs subscales of the creativity and TC score.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 92%
See 3 more Smart Citations